Rules of Origin in Services : A Case Study of Five ASEAN Countries - Fink, Carsten; Nikomborirak, Deunden (World Bank, Washington, DC, 2012)
An important question in the design of bilateral and regional free trade agreements (FTAs) covering services is to what extent nonmembers benefit from the trade preferences that are negotiated among members. This question is resolved through services rules of origin. The restrictiveness of rules of origin determines the degree of preferences entailed in market opening commitments, shaping the bargaining incentives of FTAs and their eventual economic effects. Even though the number of FTAs in services has increased rapidly in recent years, hardly any research is available that can guide policymakers on the economic implications of different rules of origin. After outlining the key economic tradeoffs and options for rules of origin in services, the paper summarizes the main findings of a research project that has assessed the rules of origin question for five countries in the ASEAN region. For selected service subsectors and a number of criteria for rules or origin, simulation exercises evaluated which service providers would or would not be eligible for preferences negotiated under a FTA. Among other findings, the simulation results point to the binding nature of a domestic ownership or control requirement and, for the specific case of financial services, a requirement of incorporation.